Th17–Related Interleukins and Parameters of Oxidative/Nitrosative Events in Childhood Asthma : Interlevkini, povezani s Th17, in parametri, povezanimi z dušikovim oksidom pri astmi otrok - Fabian, Elisabeth; Pölöskey, Peter; Kósa, Lajos; Elmadfa, Ibrahim; Attila Réthy, Lajos (Acta Medico-Biotechnica, 2021)
Purpose: Allergic asthma is a chronic lung disease with a major inflammatory component including reactive oxygen and nitrogen species in the background. The objective of this study was to investigate the relationship between the Th17-associated interleukins IL-6 and IL-10, and oxidative/nitrosative markers of stress in childhood atopic asthma.Methods: For this observational study 35 asthmatic (AG) and 21 healthy (CG) children were recruited; the volume of fractionated exhaled nitric oxide (FENO) was measured with the NIOX nitric oxide monitoring system. Plasma levels of IL-6 and IL-10 were analysed with ELISA, malondialdehyde (MDA) with HPLC.Results: Compared to healthy controls, asthmatics exhaled a significantly (p
Keywords: asthma; Th17–related interleukins; oxidative stress; nitrosative stress